PERIBAHASA ORANG BIAK DALAM ANEKA IKAN LAUT: KAJIAN FOLKLOR LISAN - Mofu, Hengki (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This research aims at digging Biak proverbs and its cultural messages contained in kinds of fish from the perspective of oral folklore. The aproach used in this research is qualitative etnography. It uses primary data taken from informat using interview and record technic. The analysis of this research reffers to Miles and Huberman theory.Based on the data analysis, it is concluded that kinds of fish used for the data contains proverbs, such as like a goat expelled into water; among apes swinging around; want to fish without using decoy; build a house in a house; prune outside, cut off sharply inside; like a chick can lay eggs; there is a shrimp behind the stone; trick ones eyes; don’t pinced if you do not want to be pinched a mouse falls into the rise storage room; walk to the limit, sail to the island: gawk while spitting. Generally, these proverbs contain some messages such as honest, heroic, generous, joyful, lovely, faithful, helpful.